Deciphering the Biological Significance of ADAR1–Z-RNA Interactions - Taisuke Nakahama (MDPI AG, 2021)
Adenosine deaminase acting on RNA 1 (ADAR1) is an enzyme responsible for double-stranded RNA (dsRNA)-specific adenosine-to-inosine RNA editing, which is estimated to occur at over 100 million sites in humans. ADAR1 is composed of two isoforms transcribed from different promoters: p150 and N-terminal truncated p110. Deletion of ADAR1 p150 in mice activates melanoma differentiation-associated protein 5 (MDA5)-sensing pathway, which recognizes endogenous unedited RNA as non-self. In contrast, we have recently demonstrated that ADAR1 p110-mediated RNA editing does not contribute to this function, implying that a unique Z-DNA/RNA-binding domain α (Zα) in the N terminus of ADAR1 p150 provides specific RNA editing, which is critical for preventing MDA5 activation. In addition, a mutation in the Zα domain is identified in patients with Aicardi–Goutières syndrome (AGS), an inherited encephalopathy characterized by overproduction of type I interferon. Accordingly, we and other groups have recently demonstrated that Adar1 Zα-mutated mice show MDA5-dependent type I interferon responses. Furthermore, one such mutant mouse carrying a W197A point mutation in the Zα domain, which inhibits Z-RNA binding, manifests AGS-like encephalopathy. These findings collectively suggest that Z-RNA binding by ADAR1 p150 is essential for proper RNA editing at certain sites, preventing aberrant MDA5 activation.